Rural dwellers’ knowledge of nutrition and their food consumption pattern in Oyo State (2009)
Lack of knowledge of available foods and their nutritional and health attributes result in inappropriate feeding practices causing malnutrition and associate problems. This study assessed rural dwellers’ knowledge of nutrition and their food consumption pattern in order to develop strategies for creating awareness on the issues of better nutrition. Three rural local government areas in Oyo state were purposively selected, out of which two wards were randomly selected from each local government area making a total of six wards. One head of household was picked from each household making a total of 156 respondents. Frequencies, percentages, Chi-square and Pearson Product Moment Correlation (PPMC) were used to describe and analyze the data. The descriptive statistics showed that the main income generating activity was farming with the average income of less than N12, 000.00 per month.. Chi-square test also showed that income (χ2 =8.292, P= 0.009) is significantly related to animal protein consumption pattern, while education has significant relationship with carbohydrate ( χ2 =16.259, P = 0.039) and vitamin (χ2 = 15.860, P = 0.044) consumption.. Finally Chi-square test revealed that there is significant relationship between constraint to adequate feeding and consumption pattern of plant protein (χ2 = 6.863, P = 0.033), animal protein (χ2 = 10.342, P = 0.039) and vitamin (χ2 = 10.243, P = 0.037). Carbohydrate based foods were the major consumed foods by the rural dwellers with few protein and insufficient vitamin. Therefore daily intake of fruits, leafy vegetables as well as other nutrients should be encouraged for proper functioning of the body system and healthy living, through nutrition awareness programme.